Projectification as a response to political demands for collaboration: A study of projects in the City of Malmö - Forssell, Rebecka; Fred, Mats; Hall, Patrik (Scandinavian Journal of Public Administration, 2013)
Many studies have shown the difficulty of managing complex, inter-organizational problems in the form of short-term projects; nevertheless the projectification of public policy continues. In this article an empirical study of the City of Malmö's project activities is conducted in order to examine the changing and stabilizing effects of projects. A further aim is to develop the political science understanding of the increased use of projects as organizational forms in public sector. A meta-study based on 30 evaluations was conducted as well as three case studies. The article shows that projects, or results and knowledge gained from projects, seldom is implemented in the permanent organization. Instead, projects tend to lead to new projects. Projects are placed in specific “parking lots”, aside from the ordinary organization, before transportation to new projects – a phenomenon which creates a degree of stability for public organizations, and which is evident in the growing number of organizations with the main task of mana- ging projects. This relative stability can be understood in terms of conflicts between different logics: a system logic (controlled by external funders) focused on the continuous creation of new projects: a political logic with the aim of demonstrating development-oriented collaboration; and an organizational logic that is focused on predictability and thus tend to repel temporary structures. One conclusion is that it is not primarily the project format that is problematic, but rather that projects tend to lead to bureaucratization as local decision-makers do not take responsibility for development.